Direct Quantification of Droplet Activation of Ambient Black Carbon Under Water Supersaturation. Issue 13 (6th July 2021) - Hu, Dawei; Liu, Dantong; Kong, Shaofei; Zhao, Delong; Wu, Yangzhou; Li, Siyuan; Ding, Shuo; Zheng, Shurui; Cheng, Yi; Hu, Kang; Deng, Zhaoze; Wu, Yunfei; et al.
Abstract: Understanding the droplet activation of black carbon (BC) under water supersaturation (SS) conditions is crucial to estimate its lifetime (through activation scavenging) and indirect radiative impacts. However, directly probing the droplet activation of ambient BC is challenging because of the difficulty in discriminating the BC‐containing particles (BCc) from other components. Here, we coupled the measurements of number concentrations between size‐resolved cloud condensation nuclei (CCN) and individual BCc, achieving a direct quantification of droplet activation for ambient BCc. The activation diameters of BCc (D50_BCc), determined as the dry diameter at which 50% of BCc were activated, were 144 ± 21 nm under SS 0.2% corresponding to activated number fraction of total BCc of 60% ± 10%. D50_BCc was determined as a function of the coating hygroscopicity, and the organic content was observed as a limiting factor in controlling BCc activation. The activated BCc number concentration was predicted using the volume‐weighted compositions within particle. The predicted CCN agreed well with the measurements for all particles, while overestimating the activated BCc number concentration by 71%, 27%, and 27% at SS = 0.1%, 0.2%, and 0.3%, respectively. The higher discrepancy under lower SS may result from the higher non‐sphericity of BCc at large sizes. Therefore, only knowing the hygroscopicity distribution of bulk compositions may not be sufficient for estimating the activation of BCc, but considering additional factors such as the non‐sphericity of BCc is necessary to estimate droplet activation. Plain Language Summary: The droplet activation of black carbon (BC) in the atmosphere is crucial for determining the amount present in cloud particles or in the interstitial phase and the consequent direct and indirect impacts on climate. The direct quantification of BC hygroscopicity remains a challenge because of the difficulty in separating BC‐containing particles (BCc) from others in the ambient environment. In this study, we concurrently measured the size‐resolved number concentration of all particles, cloud condensation nuclei, and individual BCc particles and directly quantified the droplet activation of ambient BCc under water supersaturation (SS). The results showed the activation diameter, determined as the dry diameter at which 50% of particles are activated, was 144 ± 21 nm for BCc, and a 60% ± 10% number fraction of BCc could be activated under SS = 0.2%. The direct quantification of BCc droplet activation under water SS conditions may improve the estimate of the BC lifetime and its indirect radiative impacts. Key Points: Droplet activation of ambient BC‐containing particles was found to be determined by coated size and modulated by the organic content of coatings Under SS = 0.2%, an activation diameter of 144 ± 21 nm was observed for urban BC‐containing particles (BCc), and a 60% ± 10% number fraction of BCc could be activated to cloud condensation nuclei (CCN) While Kӧhler theory CCN predictions accurately capture the total aerosol population, the CCN activation of BCc particles is overpredicted by 27%–71%